No population bias to left-hemisphere language in 4-year-olds with language impairment - Bishop, D; Holt, G; Whitehouse, A; Groen, M (PeerJ Inc., 2014)
Background: An apparent paradox in the field of neuropsychology is that people with atypical cerebral lateralization do not appear to suffer any cognitive disadvantage, yet atypical cerebral lateralization is more common in children and adults with developmental language disorders. This study was designed to explore possible reasons for this puzzling pattern of results. Methods: We used functional transcranial Doppler ultrasound (fTCD) to assess cerebral blood flow during language production in 57 four-year-olds, including 15 children who had been late-talkers when first seen at 20 months of age.We categorized cerebral lateralization as left, right or bilateral, and compared proportions with each type of laterality with those seen in a previously tested sample of children aged 6-16 years.We also compared language scores at 4 years for those with typical and atypical lateralization, and then looked at the association the opposite way: comparing those with typical or impaired language in terms of their cerebral lateralization. Results: The distribution of types of cerebral lateralization was similar for 4-year-olds to that seen in older children. Overall, cerebral lateralization was not predictive of language level. However, for children who had language difficulties at 20 months and/or 4 years (N = 21), there was no population bias to left-hemisphere language activation, whereas children without language problems at either age showed a pronounced bias to left-sided language lateralization. Nevertheless, many children with right hemisphere language had no indications of language difficulties, confirming that atypical cerebral asymmetry is not a direct cause of problems. Conclusions: We suggest that atypical lateralization at the individual level is not associated with language impairment. However, lack of lateralization at the population level is a marker of risk for language impairment, which could be due to genetic or non-genetic causes. © 2014 Bishop et al.